Formulation optimization of cabanossi made with Lama meat (Lama glama) and potato (Solanum tuberosum) using mixture design method - Ramos Ramírez, Miriam (2019)
The objective of this study was to optimize the formulation of low-fat cabanossiusing the Mix Design method (D-Optimal) from 16 cabanossi formulationscomposed of Lama glama meat (60-80%), pork fat (10-20%) and cookedpotato pulp (10-20%). The response variables were: a texture profile analysis(cohesiveness, chewiness, hardness, gumminess and springiness), chroma(C*), moisture, yield, water activity and pH. For the optimization stage, it wasconsidered minimizing the pork fat, maintaining the hardness and humidity assimilar as to those in a commercial cabanossi. The mixture design analysis setup the formulation with 72.41% of llama meat, 10.78% pork fat and 16.81%cooked potato pulp as the optimum, with 0.84 of desirability. This formulationwas validated through the experimental process and contrasted by the t-Studenttest. It confirmed the effectiveness in the prediction of the mathematical modelobtained.